2016
DOI: 10.1016/j.cryobiol.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cooling and freezing of sperm from captive, free-living and endangered squirrel monkey species

Abstract: Germoplasm banking is an important tool for the preservation of genetic material from Neotropical primates in captivity, and from free living species, especially the endangered ones like Saimiri vanzolinii (Black-headed squirrel monkey), a primate with a low incidence area (870 km(2) of floodplains) in the southern part of the Mamirauá Sustainable Development Reserve, Brazil. Therefore, in the present study we aimed to develop a sperm cryopreservation protocol comparing sperm cooling in presence (T1) and absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…However, reliable information on the most appropriate methodologies is still limited . Cryopreservation of sperm from Neotropical primates has been reported for some species, including squirrel monkeys ( Saimiri sciureus , S. boliviensis , S. collinsi , S. vanzolinii , S. cassiquiarensis , S. macrodon) , spider monkeys ( Ateles paniscus , A. marginatus ), and one species of capuchin monkey ( Sapajus apella ), tamarin ( Saguinus labiatus ), howler monkey ( Alouatta caraya ), and common marmoset ( Callithrix jacchus ) . As described for Old World monkeys, the cryoprotectants used usually contain glycerol in different concentrations—ranging from 1.5% to 8%, alone or in combination with egg yolk (used most often), or soy lecithin …”
Section: Introductionmentioning
confidence: 99%
“…However, reliable information on the most appropriate methodologies is still limited . Cryopreservation of sperm from Neotropical primates has been reported for some species, including squirrel monkeys ( Saimiri sciureus , S. boliviensis , S. collinsi , S. vanzolinii , S. cassiquiarensis , S. macrodon) , spider monkeys ( Ateles paniscus , A. marginatus ), and one species of capuchin monkey ( Sapajus apella ), tamarin ( Saguinus labiatus ), howler monkey ( Alouatta caraya ), and common marmoset ( Callithrix jacchus ) . As described for Old World monkeys, the cryoprotectants used usually contain glycerol in different concentrations—ranging from 1.5% to 8%, alone or in combination with egg yolk (used most often), or soy lecithin …”
Section: Introductionmentioning
confidence: 99%
“…Analysis of thawed samples revealed encouraging results for Neotropical primates regardless of the treatment as, for example, high total and progressive motilities and increased plasma membrane integrity (above 50%, 40%, and 80% respectively). On average, sperm cryopreserved with BB tended to show better total motility ( p = .0571), but both extenders presented greater postthaw motility than most of the values reported for Neotropical primates (Arakaki, Nichi et al, ; Carvalho, ; Leão et al, ; O'Brien et al, ; Oliveira et al, ; Silva et al, ; Valle, ; Yeoman et al, ). Additionally, we observed that there were no significant differences between extenders for most seminal parameters, excepting TBARS and intact acrosome.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, 5 of the 25 most endangered primate species in the world live in the Neotropics (Schwitzer et al, ), and yet no standard sperm cryopreservation protocols have been described for these species. In the literature a few studies have investigated sperm freezing in species like squirrel monkeys, spider monkeys, howler monkey, capuchin monkey, marmosets, and tamarins (Arakaki, Nichi et al, ; Carvalho, ; Denis, Poindexter, Ritter, Seager, & Deter, ; Leão et al, ; Morrell et al, ; O'Brien, Hollinshead, Evans, Evans, & Maxwell, ; Oliveira et al, ; Oliveira, Leão, Almeida, Santos, & Domingues, ; Sankai, Tsuchiya, Ogonuki, Cho, & Yoshikawa, ; Silva et al, ; Yeoman, Ricker, Hossain, & Abee, ). However, the variety of protocols and their respective outcomes (Table ) makes it difficult to reach a consensus regarding an ideal method designed to routinely cryopreserve sperm from these primates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of sperm in the seminal coagula of some primate species living in multimale–multifemale social organizations (Dixson & Anderson, ), such as squirrel monkeys ( Saimiri sciureus , Linnaeus, ) has not yet been reported (Bennet, ), leading to the conclusion that this coagulum has no fertilization properties. On the contrary, in other species with similar mating systems, such as spider monkeys ( Ateles geoffroyi , Kuhl, ) (Hernández‐López et al, ), tufted capuchin monkeys ( Sapajus apella , Linnaeus, ) (Leão et al, ; Oliveira et al, ), and squirrel monkeys (Oliveira, Leão, Almeida, Santos, & Domingues, ; Oliveira et al, ,), seminal coagulum possesses high sperm concentrations. In fact, these coagulated fractions have been shown to possess higher sperm concentrations than the non‐coagulated fractions of the ejaculate (Oliveira et al, ).…”
Section: Introductionmentioning
confidence: 99%